Formulating A Value Proposition Strategy For Herbal Product Retail Business: A Case Study Of DHC Herbal Product Retail Store - Syarifudin, Nurdiana; Sahela, Kharisa Zeisha (Universitas Dehasen Bengkulu, 2025)
This study aims to formulate an effective value proposition strategy for herbal product retail businesses, encompassing both online and offline stores. The research focuses on how companies can develop attractive and relevant value propositions for consumers in the context of a competitive digital market. This study employs a qualitative approach using a case study analysis. Data were collected through interviews with the management of DHC Herbal Product Retail Store and its consumers, as well as an analysis of the company’s digital strategy and proposed value proposition. The findings reveal that DHC Herbal Product Retail Store can enhance its value proposition by emphasizing product quality, authenticity, health benefits aligned with consumer needs, and the strategic use of social media and digital platforms. The main contribution of this study is the development of a value proposition strategy tailored for herbal product retail businesses. This approach offers new insights into designing value propositions that align with the evolving online and offline market dynamics. The practical implications of this research highlight the importance for herbal product retail businesses to continuously adapt their value propositions to market changes and consumer demands, in order to improve customer loyalty and competitiveness.